Interface Charges Influence on the Subthreshold Region from Triple Gate SOI FinFET to Omega-Gate Nanowire Devices - Silva, V. C. P.; Martino, J. A.; Agopian, P. G. D. [UNESP]; IEEE (Ieee, 2018)
In this paper, the influence of interface charges (fixed charges and interface traps) on the subthreshold region was analyzed focusing on the fin height. This influence was analyzed from Triple gate SOI FinFETs (devices with a high silicon height - h(fin)) to Omega-Gate Nanowires (with a small h(fin)). The results shows that as the h(fin) height becomes smaller, the influence of interface charges is reduced due to the better electrostatic coupling. When the fin height becomes small enough, the interface charges did not influence both subthreshold swing and threshold voltage, even for wide devices, thanks to the supercoupling.